DNA methylation signatures follow preformed chromatin compartments in cardiac myocytes - Stephan Nothjunge (Nature Portfolio, 2017)
Chromatin is organized in higher order A and B compartments, reflecting active and inactive chromatin. Here, the authors provide evidence that in cardiac myocytes DNA methylation is established in preformed chromatin compartments and may be dispensable for higher order chromatin organization.